Is Characteristic Frequency Limiting Real-Time Electrocochleography During Cochlear Implantation? - Walia, Amit; Shew, Matthew A.; Lefler, Shannon M.; Kallogjeri, Dorina; Wick, Cameron C.; Holden, Timothy A.; Durakovic, Nedim; Ortmann, Amanda J.; Herzog, Jacques A.; Buchman, Craig A. (Frontiers in Neuroscience, 2022)
Electrocochleography (ECochG) recordings during cochlear implantation have shown promise in estimating impact on residual hearing. The purpose of the study was (1) to determine whether a 250-Hz stimulus is superior to 500-Hz in detecting residual hearing decrement and if so; (2) to evaluate whether crossing the 500-Hz tonotopic, characteristic frequency (CF) place partly explains the problems experienced using 500-Hz. Multifrequency ECochG comprising an alternating, interleaved acoustic complex of 250- and 500-Hz stimuli was used to elicit cochlear microphonics (CMs) during insertion. The largest ECochG drops (≥30% reduction in CM) were identified. After insertion, ECochG responses were measured using the individual electrodes along the array for both 250- and 500-Hz stimuli. Univariate regression was used to predict whether 250- or 500-Hz CM drops explained low-frequency pure tone average (LFPTA; 125-, 250-, 500-Hz) shift at 1-month post-activation. Postoperative CT scans were performed to evaluate cochlear size and angular insertion depth. For perimodiolar insertions (N=34), there was a stronger linear correlation between largest ECochG drop using 250-Hz stimulus and LFPTA shift (r=0.58), compared to 500-Hz (r=0.31). The 250- and 500-Hz CM insertion tracings showed an amplitude peak at two different locations, with the 500-Hz peak occurring earlier in most cases than the 250-Hz peak, consistent with tonotopicity. When using the entire array for recordings after insertion, maximum 500-Hz response was observed 2-6 electrodes basal to the most-apical electrode in 20 cases (58.9%). For insertions where the apical insertion angle is >350° and the cochlear diameter is <9.5 mm, the maximum 500-Hz ECochG response may occur at the non-apical most electrode. For lateral wall insertions (N=14), the maximum 250- and 500-Hz CM response occurred at the most-apical electrode in all but one case. Using 250-Hz stimulus for ECochG feedback during implantation is more predictive of hearing preservation than 500-Hz. This is due to the electrode passing the 500-Hz CF during insertion which may be misidentified as intracochlear trauma; this is particularly important in subjects with smaller cochlear diameters and deeper insertions. Multifrequency ECochG can be used to differentiate between trauma and advancement of the apical electrode beyond the CF.